Od Ostroroga do „Pszczelnictwa Współczesnego” – zarys wielkopolskiego piśmiennictwa pszczelniczego - Tomaszewski, Roman (Biblioteka Uniwersytecka w Poznaniu, 2013)
Początki wielkopolskiego piśmiennictwa pszczelniczego związane są z działalnością Jana Ostroroga i pierwszą polską książką pszczelarską, Nauką koło pasiek, wydaną w 1614 roku. Prawdziwie bujny rozwój oświaty pszczelarskiej, w tym literatury, rozpoczyna się jednak dopiero od połowy XIX wieku. Pierwszym wielkopolskim czasopismem dla hodowców pszczół był wychodzący od 1880 roku „Pszczelarz”. Wcześniej chcący pisać o tej gałęzi gospodarki umieszczali swe publikacje na łamach różnych czasopism, często dalekich swą tematyką od zagadnień gospodarstwa wiejskiego. Biorąc pod uwagę bogactwo poruszonego tematu, a przy tym objętość jednego artykułu, starano się w nim przedstawić ważniejsze dzieła książkowe i czasopisma, a jednocześnie w miarę możliwości ludzi, którzy często prócz związków z pszczelarstwem zapisali się dzięki swej różnorodnej działalności na kartach historii regionu. Szczególną uwagę zwrócono na czasopisma dziedzinowe, których liczba i jakość pozwalają stwierdzić, że Wielkopolska miała duży wkład w rozwój tego działu czasopiśmiennictwa w skali krajowej. Literatura pszczelarska nie rozwijała się w pustce politycznej, gospodarczej czy kulturowej. Dlatego przedstawiony został też rozwój organizacji pszczelarskich i innych niż piśmienne metod przekazu wiedzy teoretycznej i praktycznej.

The presentation aims at providing a comprehensive overview of the history of the apicultural literature written in the region until 1950. Its beginnings are closely related to the achievements of Jan Ostroróg and the first Polish beekeeping manual, Nauka koło pasiek, published in 1614. Genuinely flourishing development of beekeeping education and its relevant literature started though dated as late as the half of the nineteenth century. The first journal for beekeepers published in Greater Poland was “Pszczelarz” (the first issue was published in 1880). Earlier, authors of apicultural articles had had to publish their publications in other jo urnals, oftentimes representing subjects remotely related to issues of rural livelihood and economy. Taking into consideration the diversity and richness of the subject presented in this article, as well as the limitations imposed by its required size, the author attempts to discuss only the most important books and periodicals covering the subject. Furthermore, a short presentation of people who, beside their relations to apiculture, also had their notable share in the achievements in the local history of the region, is provided. A particular attention is given to periodicals covering the subject area whose sheer circulation and the quality they represented testify to the enormous regional contribution of Greater Poland to the development of the literature of this type in the whole of the country. The apicultural literature was not, however, developing in political, economic and cultural void. Hence, the development of apicultural organizations and associations as well as other than written transfer of knowledge (theoretical and practical) of records of indigenous human knowledge are also presented and discussed.
From Jan Ostroróg to „Pszczelnictwo Współczesne” – an outline of apicultural (beekeeping) literature from the Wielkopolska region (Greater Poland)
Keywords: pszczelarstwo; bibliografia; Wielkopolska; apiculture; bibliography; Greater Poland (the Wielkopolska region)